Analysis of electric energy commercial metering system influencing on energy supply company operating characteristics - Zorkin A.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2007)
Input electric energy statistic information for network as well as electric energy losses in the networks of the energy supply company for 2002-2005 years is analyzed. Influencing of electric energy commercial metering system implementation on electric energy losses decreasing in energy supply company network is determinate.